Landfill leachate treatment by electrochemical oxidation - Bashir, M.J.K.; Isa, M.H.; Awang, Z.B.; Aziz, H.A.; Kutty, S.R.M.; Mohajeri, S.; Farooqi, I.H. (2009)
This study investigated the electrochemical oxidation of stabilized leachate from Pulau Burung semi-aerobic sanitary landfill by conducting laboratory experiments with sodium sulfate Na2SO4 (as electrolyte) and graphite carbon electrodes. The control parameters were influent COD, current density and reaction time, while the responses were BOD removal, COD removal,BOD:COD ratio, color and pH. Na2SO4 concentration was 1 g/L. Experiments were conducted based on a three-level factorial design and response surface methodology (RSM) was used to analyze the results. The optimum conditions were obtained as1414 mg/L influent COD concentration, 79.9 mA/cm2 current density and 4 h reaction time. This resulted in 70% BOD removal, 68% COD removal, 84% color removal, 0.04 BOD/COD ratio and 9.1 pH. Electrochemical treatment using graphite carbon electrode was found to be effective in BOD, COD and color removal but was not effective in increasing the BOD/CODratio or enhancing biodegradability of the leachate. The color intensity of the treated samples increased at low influent COD and high current density due to corrosion of electrode material.